Sosialisasi Hukum Tentang Sanksi Hukum Bagi Pelaku Tawuran Antar Remaja - Suriani Suriani; Angela Ekklesia Siagian; Himmatul Ummi Harahap; Nanda Prayoga; Muhammad Fadli Elza Ms; Rado Maruli Malau (FKIP, Universitas Palangka Raya, 2024)
This study aims to investigate the effectiveness of legal socialization regarding legal sanctions for adolescents involved in teenage brawls. Teenage brawls pose a serious threat to the safety and well-being of adolescents and the surrounding community. In this context, legal socialization is crucial to enhance adolescents' understanding of the legal consequences of engaging in brawls and reduce brawl incidents in their environment. The research method employed is a qualitative approach, gathering data through participant observation and interviews with adolescents involved in brawls, as well as relevant parties such as teachers, parents, and security officers. The findings indicate that legal socialization has a positive impact on increasing adolescents' awareness of the legal sanctions they face if involved in brawls. Furthermore, legal socialization plays a role in changing adolescents' attitudes and behaviors towards violence and enhancing their understanding of the importance of resolving conflicts peacefully. This study highlights the importance of a preventive approach involving legal socialization in addressing the issue of teenage brawls. By enhancing adolescents' awareness of the legal sanctions they may face, it is hoped to help reduce brawl incidents and create a safer environment for adolescents and the community. Therefore, the findings of this research make a significant contribution to efforts to prevent adolescent violence and protect adolescent well-being in society.